A review of fertilization assessment methods in oil palm plantation - Mat Su, Ahmad Suhaizi; Tan, Shu Qing (Malaysian Society of Agricultural Engineers, 2019)
Rising in production cost due to labour shortage, low efficiency of farm operation, low yield, and increase in input cost of materials were among the key factors faced by Malaysian oil palm industry. Thus, significantly affect the overall upstream performance and the annual budget for the plantation operation. Input cost, especially fertilizer accounted for more than 50% of the production cost annually. Highly weathered tropical soil, intensive and mono-cropping farming activities caused nutrient depletion over the availability of the nutrient to the plant. Among the agronomic practices, fertilizer application and saving become a limitation due to its increasing share of production cost, thus effect the annual targeted yield. Prior to the fertilizer application and recommendation rate, a proper fertilizer assessment program should be conducted for achieving economic, social and environmental sustainability. In this paper, several methods of fertilizer assessment for oil palm plantation were identified and discussed based upon the agronomic practices. In addition, the several techniques under proximal sensing technology for Precision Agriculture (PA) program to quantify the fertility and crop response also were listed. The adaptation of the technology and a new approach in reducing the fertilizer used will lead the input cost reduction in oil palm plantation while improves overall farm efficiency.